International Dimensions and Trends in Higher Education in Troubled Times : Insights from Key Global Publications 2018-2023 in International Higher Education - Altbach, Philip G.; Wang, Lizhou; Wit, Hans de (Educational Research E-Books Online, Collection 2024., 2025)
This book features a carefully curated collection of articles drawn from the quarterly International Higher Education (IHE). Focused on the international dimensions and trends in higher education, these articles offer valuable insights into the tumultuous events spanning from January 2018 to December 2023. This volume offers a comprehensive discussion of key international themes covering a period of great turmoil in global higher education in a series of short, targeted articles. The five-year period is marked by the geopolitical tensions and internationalization issues at both national and international levels, in the middle of a global pandemic. We provide readers with a coherent organization of articles, grouped into ten themes that relate to the most central issues facing international(ization of) higher education, which are relevant today and in the future. While readers of the higher education research community will find these themes familiar, this book is also tailored for a more diverse audience. Policymakers and practitioners worldwide will find this book helpful when seeking a comprehensive and approachable guide to navigating the complexities of international dimensions and trends in higher education. This collection is a valuable resource for courses worldwide that focus on global issues and the internationalization of higher education. See Less